2016
DOI: 10.4269/ajtmh.15-0640
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Pentamidine: A Novel Therapy for Single Lesions of Bolivian Cutaneous Leishmaniasis

Abstract: Abstract. A novel therapy, intralesional (IL) pentamidine, was compared to intralesional therapy with antimony (ILSb), a World Health Organization-recommended therapy, for single Bolivian Leishmania braziliensis lesions. In Study 1, 90 patients were randomized equally between three injections of ILSb over 5 days, five injections of ILSb over 11 days, and three injections of IL pentamidine (120 μg/mm 2 lesion area [ILPenta-120-3]) over 5 days. Cure rates at 6 months were 57% for ILSb-3 injections, 73% for ILSb-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…15,[17][18][19] Using pentamidine IL, a cure rate of 73% was achieved. 16 The present study was superior in effectiveness probably because it was applied to papular lesions of the clinical LRC variant, whereas in the aforementioned studies, it was performed in the ulcerous form. In LRC, the lesions are small circumscribed papules and are easily infiltrated completely with the drug, conditions that can favor the cure.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…15,[17][18][19] Using pentamidine IL, a cure rate of 73% was achieved. 16 The present study was superior in effectiveness probably because it was applied to papular lesions of the clinical LRC variant, whereas in the aforementioned studies, it was performed in the ulcerous form. In LRC, the lesions are small circumscribed papules and are easily infiltrated completely with the drug, conditions that can favor the cure.…”
Section: Discussionmentioning
confidence: 89%
“…Studies have been published from Bolivia where CL ulcerative lesions caused by Leishmania braziliensis were treated intralesionally (IL) with Meglumine Antimoniate (MA) and pentamidine, reporting a cure rate of 70% and 73%, respectively. 15,16 In Brazil, studies reported a cure rate of 80%, 83.3%, and 77.7% in patients with the ulcerative variant of CL. [17][18][19] Reported here are the results of a study conducted in the subtropical region of the province of Pichincha of Ecuador where 21 patients with LRC lesions were treated IL with MA.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with contraindications to systemic treatment, however, can benefit from IL MA treatment 3,8 . Recently, Soto et al 9 found that treatment with IL MA has comparable efficacy to treatment with IL pentamidine in Bolivian patients with cutaneous leishmaniasis caused by L. braziliensis.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2013 publication, cure rates were 70% (21 of 30) for three intralesional injections of antimony, 20% (4 of 20) for cryotherapy, and 17% (5 of 30) for a placebo cream. 2 In a 2016 publication, cure rates were 57% (17 of 30) for three intralesional injections of antimony, 70% (42 of 60) for five intralesional injections of antimony, and 70% (43/60) for three intralesional injections of pentamidine. 3 At present, classic pentavalent antimony has a cure rate of 81% (116 of 144: J. Soto, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%